What causes in vivo muscle specific tension to increase following resistance training? - Erskine, R. M.; Jones, D. A.; Maffulli, N.; Williams, A. G.; Stewart, C. E.; Degens, H. (Experimental Physiology, 2011)
It is not known why in vivo muscle specific tension increases following resistance training in humans but changes in muscle fibre-type composition, increased single-fibre specific tension or lateral force transmission might provide explanations. Lateral force transmission would increase specific tension but decrease contraction velocity, thus not affecting maximal power per unit muscle volume. In vivo muscle specific tension, power output and muscle volume were determined in the quadriceps femoris of 42 young men, while myosin heavy chain (MyHC) isoform composition, single-fibre (SF) specific tension, SF maximal shortening velocity (Vmax) and SF peak power (Wmax) of the vastus lateralis were established in a subsample (n = 17) before and after high-intensity leg-extension resistance training (3 sessions week-1 for 9 weeks). Following training, in vivo muscle specific tension increased by 17% but the power output/muscle volume ratio remained unaltered. Furthermore, there was no relationship between the training-induced decrease in MyHC IIX and the change in specific tension in vivo. In addition, SF specific tension, Vmax and Wmax were unchanged following training. In conclusion, a change in fibre-type composition does not explain the increased in vivo specific tension, nor does it seem likely that increased myofilament packing occurred with resistance training. However, an unchanged in vivo power per unit muscle volume is in accordance with the notion of enhanced lateral force transmission after strength training.